Synthesis, characterization and charge storage properties of π-biindolo[2, 3-b]quinoxaline for solution-processing organic transistor memory. (August 2019) - Zhao, Jianfeng; Li, Hairong; Li, Huanqun; Zhao, Qiang; Ling, Haifeng; Li, Jiewei; Lin, Jinyi; Xie, Linghai; Lin, Zongqiong; Yi, Mingdong; Huang, Wei
Abstract: A novel asymmetrical biindolo[2, 3- b ]quinoxaline derivative (IQIQ ) was prepared via the CuI catalysed C-N Ullmann coupling method and fully characterized. For comparison, two solution-processing organic transistor memory devices (A and B) were constructed. In device A with IQIQ, the parameters of large memory window (48 V) but weak on/off current ratio (∼10 1 at 10 4 s) indicated the good hole trapping ability determined by the matched HOMO level but weak endurance property of IQIQ . Meanwhile, device B with PS blended IQIQ presented not only similar large memory window but also apparently improved the hole endurance property of IQIQ determined by the blending material which intrinsically acted as the bifunctional tunneling:floating gate layer. Graphical abstract: Image 1 Highlights: New biindolo[2, 3- b ]quinoxaline (IQIQ ) was obtained via Ullmann method and fully characterized. Device A (pure IQIQ ) performed large memory window (48 V) but weak on/off ratio (∼10 1 at 10 4 s). Device B (IQIQ:PS) performed better with memory window as 51 V, on/off current ratio as ∼10 3 (10 4 s). Better Device B (IQIQ :PS) was distributed to the blended bifunctional tunneling:floating gate. I QIQ :PS blend would be a kind of potential useful charge storage material.